2012
DOI: 10.4238/2012.june.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of expressed sequence tags from semimembranosus muscle of commercial and naturalized pig breeds

Abstract: ABSTRACT. In general, genetic differences across different breeds of pig lead to variation in mature body size and slaughter age. The Commercial breeds Duroc and Large White and the local Brazilian breed Piau are ostensibly distinct in terms of growth and muscularity, commercial breeds are much leaner while local breeds grow much slower and are fat type pigs. However, the genetic factors that underlie such distinctions remain unclear. We used expressed sequence tags (ESTs) to characterize and compare transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown breed differences in mitochondrial function in muscle and fat in the pig [27,28]. The transcript profiling of ESTs from the semimembranosus muscle demonstrates elevated expression of mitochondrial related enzymes (NADH dehydrogenase, cytocrome c oxidase and cytocrome b reductase) in the skeletal muscle of Piau, a naturalized Brazilian pig breed with slow growth rate, high fat deposition and favorable meat quality, compared to commercial breeds (Large White and Duroc), implicating breed differences in oxidative and glycolytic metabolism [29]. Similar breed differences were reported in Korean native pigs who demonstrate higher expression of the 3 mitochondrial proteins: succinate dehydrogenase, NADH-ubiquinone oxidoreductase, and glycerol-3-phosphate dehydrogenase in the muscle as compared with Landrace [4].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown breed differences in mitochondrial function in muscle and fat in the pig [27,28]. The transcript profiling of ESTs from the semimembranosus muscle demonstrates elevated expression of mitochondrial related enzymes (NADH dehydrogenase, cytocrome c oxidase and cytocrome b reductase) in the skeletal muscle of Piau, a naturalized Brazilian pig breed with slow growth rate, high fat deposition and favorable meat quality, compared to commercial breeds (Large White and Duroc), implicating breed differences in oxidative and glycolytic metabolism [29]. Similar breed differences were reported in Korean native pigs who demonstrate higher expression of the 3 mitochondrial proteins: succinate dehydrogenase, NADH-ubiquinone oxidoreductase, and glycerol-3-phosphate dehydrogenase in the muscle as compared with Landrace [4].…”
Section: Discussionmentioning
confidence: 99%
“…The ESTs used in this study were generated from three different pig breeds' skeletal muscle tissue cDNA libraries (Duroc, Large White and a Local Breed Piau) constructed by Nascimento et al (2012).…”
Section: Est Datasetmentioning
confidence: 99%
“…Functional annotation of ESTs for the three datasets was performed using the program BLASTX (Altschul et al 1997), against the data base of transcripts from SwissProt (http://www.expasy.ch/sprot/). More details can be obtained at Nascimento et al (2012).…”
Section: Differentially Expressed Genes Identificationmentioning
confidence: 99%
See 2 more Smart Citations